Collusion in growing and shrinking markets: Empirical evidence from experimental duopolies - Klaus Abbink; Jordi Brandts (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2005)
We study collusive behaviour in experimental duopolies that compete in prices under dynamic demand conditions. In one treatment the demand grows at a constant rate. In the other treatment the demand declines at another constant rate. The rates are chosen so that the evolution of the demand in one case is just the reverse in time than the one for the other case. We use a box-design demand function so that there are no issues of finding and co-ordinating on the collusive price. Contrary to game-theoretic reasoning, our results show that collusion is significantly larger when the demand shrinks than when it grows. We conjecture that the prospect of rapidly declining profit opportunities exerts a disciplining effect on firms that facilitates collusion and discourages deviation.
Keywords: C90; C72; D43; D83; L13; 330; Laboratory experiments; industrial organisation; oligopoly; price competition; collusion; Kartell; Oligopol; Preisabsprache; Duopol; Test